Entrepreneurship Barrier and Motivations: Perception of Lincoln University Commerce Students - Roudaki, Jamal (Accounting Department,, 2010)
The ambitious of being own boss and run independent own-business is widespread among university graduates. However, there are some barrier and motivations that hinder or accelerate this thrust. This paper investigates students’ perceptions about impediment and stimulation of entrepreneurial activities. A sample of commerce students responds to a questionnaire survey. Results indicate that gender, age and working status of students are not significantly correlated with their perception about barrier and motivation factors of the research study. Nevertheless, financial risk and fear from failure are the most and the least important barriers respectively. University level programmes and personal experience are the most motivation factors while media and government supports are at the bottom of the list of priority of such factors. Respondents believe that entrepreneurs are good in accounting, financial analysis and having good skills and these factors are important in preparation of crating new business. Keywords: entrepreneurship, student attitudes, entrepreneurial motivation, barrier